الولاية المنتدبة بين الإستقلالية والرقابة - بشرى بن مالك; محمد إلياس العايبي (My University, 2020)
Summary of the study: According to Article 02 of State Law 12-07, the state has two bodies: the State People’s Council and the Governor. The Council has broad powers in many fields, and this is what Articles 73 to 101 stipulate. It is composed of a group of elected officials who were chosen and recommended by the residents. The state is from among a group of candidates proposed by parties or liberal candidates, and therefore it is formed only from the category of delegates, and the number of members of the state popular councils changes according to the change in the state’s population resulting from the process of the national census of housing and population and within the conditions stipulated According to Article 82 of Organic Law No. 16-10 relating to the election system, the law authorized members of the State People’s Assembly to establish temporary committees to carry out a task determined by the Council, such as, for example, the task of investigating a specific matter pertaining to a state institution or violations at the level of an interest affiliated with the state or others, and accordingly Committees are divided into permanent and permanent Other special. Of course, the Council has someone to manage it, chair its meetings, summon it, and represent it in ceremonial ceremonies and official demonstrations. He is the President of the State People’s Council, who selects his deputies and presents them to the Council for approval. He is elected from among its members, with the necessity of respecting the conditions related to the electoral list, and he has powers mentioned in State Law 12-07. The executive body, represented by the governor, who is appointed by a presidential decree taken in the Council of Ministers based on a report from the Minister of the Interior in accordance with Article 78 of the Constitution, and whose duties may end for any reason in the same manner, has many and varied powers, and the state law is not only considered a source of them, but In addition to that, there is the National Property Law, the Election Law, the Civil Status Law, and other laws, so it has a complex and distinct status. In the subject of our study, we discussed the new administrative division in Algeria, which is the establishment of administrative districts, as Algeria knew this organization under the system of the Greater Algiers Governorate. The creation of administrative districts is considered one of the most important topics that have occupied the media for some time. After the administrative districts were just a project in 2010, it became a Implementation in 2015, when two decrees were issued in this regard. The first was Presidential Decree No. 15-140, which included the creation of provinces. The second was Executive Decree No. 15-141, which included the organization and functioning of administrative provinces, which included the creation of 10 administrative provinces at the level of 08 states in southern Algeria, run by delegated governors who are appointed. By the President of the Republic, pursuant to a presidential decree, where he exercises his duties under the authority of the governor of the state to which the administrative district belongs, in order to achieve a number of goals, including bringing the administration closer to the citizen and reducing the burden on the state. ...................... ملخص الدارسة : طبقا للمادة 02 من قانون الولاية 12-07 ، للولاية هيئتان المجلس الشعبي الولائي و الوالي ، و للمجلس اختصاصات واسعة في مجالات عديدة و هذا ما نصت عليه المواد من 73 إلى 101 ، يتشكل من مجموعة منتخبين تم اختيارهم و تزكيتهم من قبل سكان الولاية من بين مجموعة من المترشحين المقترحين من قبل الاحزاب أو المرشحين الأحرار، و عليه فإنه يتشكل فقط من فئة المنتدبين، كما أنه يتغير عدد أعضاء المجالس الشعبية الولائية حسب تغير عدد سكان الولاية الناتج عن من عملية الإحصاء الوطني للسكن و السكان و ضمن الشروط التي نصت عليها المادة 82 من القانون العضوي رقم 16-10 المتعلق بنظام الانتخابات، خوﱠل القانون لأعضاء المجلس الشعبي الولائي إنشاء لجان مؤقتة تتولى القيام بمهمة يحددها المجلس كأن مثلا مهمة التحقيق في أمر معين يخص مؤسسة ولائية أو تجاوزات على مستوى مصلحة تابعة للولاية و غيرها، و عليه تنقسم اللجان إلى دائمة و أخرى خاصة. و بطبيعة الحال للمجلس من يديره و يرأس إجتماعاته و يستدعيه و يمثله في الإحتفالات التشريفية و التظاهرات الرسمية، وهو رئيس المجلس الشعبي الولائي الذي يقوم بإختيار نوابه و يعرضهم على المجلس للمصادقة عليه. و يتم إنتخابه من بين أعضاءه مع ضرورة إحترام الشروط المتعلقة بالقائمة الإنتخابية وله صلاحيات ذكرت في قانون الولاية 12-07 . و الهيئة التنفيذية المتمثلة في الوالي الذي يعين بموجب مرسوم رئاسي يتخذ في مجلس الوزارء بناءا على تقرير من وزير الداخلية طبقا للمادة 78 من الدستور و قد تنتهي مهامه لسبب من الاسباب بنفس الكيفية، له صلاحيات كثيرة و متنوعة، ولا يعتبر قانون الولاية فقط مصدرا لها بل إلى جانب ذلك هناك قانون الاملاك الوطنية و قانون الانتخابات و قانون الحالة المدنية و غيرها من القوانين فهو بذلك يتمتع بوضعية مركبة و متميزة. وتناولنا في موضوع دراستنا التقسيم الاداري الجديد في الجزائر ألا وهو إنشاء المقاطعات الإدارية ، إذ عرفت الجزائر هذا التنظيم في ظل نظام محافظة الجزائر الكبرى ويعتبر استحداث المقاطعات الإدارية من أهم المواضيع التي شغلت وسائل الإعلام منذ فترة فبعدما كانت المقاطعات الإدارية مجرد مشروع سنة 2010 أ أصبح حيز التنفيذ سنة 2015 حيث صدر مرسومين في هذا الشأن الاول المرسوم الرئاسي رقم 15-140 المتضمن استحداث مقاطعات اما الثاني المرسوم التنفيذي رقم 15- 141 المتضمن تنظيم المقاطعات الإدارية وسيرها حيث تضمنا استحداث 10 مقاطعات إدارية على مستوى 08 ولايات بالجنوب الجزائري يسيرها ولاة منتدبون حيث يتم تعيينهم من طرف رئيس الجمهورية بموجب مرسوم رئاسي حيث يمارس مهامه تحت سلطة والي الولاية التي تتبعها المقاطعة الإدارية وذلك لتحقيق جملة من الأهداف من بينها تقريب الإدارة من المواطن وتخفيف العبء على الولاية. .................. Résumé de l'étude : Conformément à l'article 02 de la loi de l'État 12-07, l'État est composé de deux organes : le Conseil populaire de l'État et le Gouverneur. Le Conseil dispose de larges pouvoirs dans de nombreux domaines, et c'est ce que stipulent les articles 73 à 101. est composé d'un groupe d'élus choisis et recommandés par les habitants. L'État est formé parmi un groupe de candidats proposés par des partis ou des candidats libéraux, et donc il est formé uniquement de la catégorie des délégués et du nombre de membres des conseils populaires de l'État évolue en fonction de l'évolution de la population de l'État résultant du processus de recensement national de l'habitat et de la population et dans les conditions stipulées. Selon l'article 82 de la loi organique n° 16-10 relative au régime électoral, le la loi autorise les membres de l'Assemblée populaire de l'État à créer des commissions temporaires pour accomplir une tâche déterminée par le Conseil, comme, par exemple, la tâche d'enquêter sur une affaire spécifique relative à une institution de l'État ou des violations au niveau d'un intérêt affilié à l'État ou d'autres, et par conséquent les comités sont divisés en comités permanents et permanents Autre spécial. Bien entendu, le Conseil a quelqu'un pour le gérer, présider ses réunions, le convoquer et le représenter dans les cérémonies cérémonielles et les manifestations officielles. Il s'agit du Président du Conseil populaire d'État, qui sélectionne ses adjoints et les présente au Conseil pour approbation. . Il est élu parmi ses membres, avec la nécessité de respecter les conditions liées à la liste électorale, et il dispose des pouvoirs mentionnés dans la loi de l'État 12-07. L'organe exécutif, représenté par le gouverneur, nommé par décret présidentiel pris en Conseil des ministres sur rapport du ministre de l'Intérieur conformément à l'article 78 de la Constitution, et dont les fonctions peuvent prendre fin pour toute raison en de la même manière, a des pouvoirs nombreux et variés, et la loi de l'État est non seulement considérée comme une source de ceux-ci, mais en plus de cela, il y a la loi sur la propriété nationale, la loi électorale, la loi sur l'état civil et d'autres lois, donc elle a un statut complexe et distinct. Dans le cadre de notre étude, nous avons évoqué le nouveau découpage administratif en Algérie, qui est la création de circonscriptions administratives, comme l'Algérie a connu cette organisation sous le système du Gouvernorat du Grand Alger. La création de circonscriptions administratives est considérée comme l'une des plus importantes. Des sujets qui ont occupé les médias pendant un certain temps. Après que les circonscriptions administratives n'étaient qu'un projet en 2010, elles sont devenues une mise en œuvre en 2015, lorsque deux décrets ont été publiés à cet égard. Le premier était le décret présidentiel n° 15-140, qui comprenait la création des provinces. Le deuxième était le décret exécutif n°15-141, qui portait sur l'organisation et le fonctionnement des provinces administratives, qui comprenait la création de 10 provinces administratives au niveau de 08 États dans le sud de l'Algérie, dirigées par des gouverneurs délégués qui sont nommé. Par le Président de la République, en vertu d'un décret présidentiel, où il exerce ses fonctions sous l'autorité du gouverneur de l'État auquel appartient la circonscription administrative, afin d'atteindre un certain nombre d'objectifs, notamment le rapprochement de l'administration pour le citoyen et réduire le fardeau de l'État.